Isolation, identification, and characterization of resistant bacteria to antibiotics from pharmaceutical effluent and study of their antibiotic resistance - Mahmud, Md. Shahin; Hosen, Md. Aoulad; Hossion, Md. Ishaq; Sadik Sabuj, Md. Shiblee; Rumi, Nazmi Ara; Hossain, Md. Khaled; Dauelbait, Musaab; Nafidi, Hiba-Allah; Dawoud, Turki M.; Ibrahim, Muhammad; Bourhia, Mohammed (Frontiers in Microbiology, 2023)
Pharmaceutical effluents primarily enter aquatic environments through the discharge of treated and untreated wastewater from various sources, including hospitals, pharmaceutical manufacturing facilities, and households. Microbes sourced from pharmaceutical effluents such as Pseudomonas spp. pose a significant public health concern because of their high levels of resistance to multiple drugs and extreme multidrug resistance.Therefore, the present study was conducted for the isolation, identification, and molecular characterization of selected isolates from pharmaceutical effluents and also determined their antibiotic sensitivity patterns. From June 2016 to March 2017, a study was conducted on four well-known pharmaceutical companies specializing in antibiotic production in Dhaka and Gazipur. Four wastewater samples were collected from various origins and then brought to the Bacteriology laboratory for microbiological examination.Twelve pure isolates were obtained and characterized through cultural and biochemical tests while molecular identification of Pseudomonas spp. was performed using the 16S rRNA gene sequence.Twelve commercially available antibiotics were used for antibiotic sensitivity tests using Kirby-Bauer disc diffusion methods. We isolated the most predominant isolates, P. aeruginosa (41.67%), followed by Bacillus spp. (33.33%) and Staphylococcus spp. (25%) respectively. Among 12 antibiotics, ciprofloxacin is 100% sensitive against P. aeruginosa, while the remaining 11 antibiotics are 100% resistant. Bacillus spp.showed 100% resistance to all antibiotics while 50% sensitive to vancomycin and 100% to chloramphenicol, respectively. Staphylococcus spp. was 100% resistant to all antibiotics. Our research suggested that P. aeruginosa is the reservoir of antibiotic resistance genes and spreads disease to humans from the environment. The findings of this study i.e the isolation, identification, and characterization of antibiotic-resistant bacteria from pharmaceutical effluent have highlighted, comprehended, and mitigated the dissemination of antibiotic resistance and opportunistic bacteria.